2019
DOI: 10.1186/s13578-019-0360-5
|View full text |Cite
|
Sign up to set email alerts
|

Autologous mitochondrial microinjection; a strategy to improve the oocyte quality and subsequent reproductive outcome during aging

Abstract: Along with the decline in oocyte quality, numerous defects such as mitochondrial insufficiency and the increase of mutation and deletion have been reported in oocyte mitochondrial DNA (mtDNA) following aging. Any impairments in oocyte mitochondrial function have negative effects on the reproduction and pregnancy outcome. It has been stated that infertility problems caused by poor quality oocytes in women with in vitro fertilization (IVF) and repeated pregnancy failures are associated with aging and could be ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 79 publications
(137 reference statements)
1
35
0
Order By: Relevance
“…Understanding the large impact of abnormal mitochondrial function on oocyte and embryo development has also led to new research looking at the effects of mitochondria replacement therapy. The thought behind these techniques, which can include pronuclear transfer, spindle transfer, ooplasm transfer, or mitochondrial microinjection, is that the mutant or defective mitochondria can be replaced or augmented with healthy donor mitochondria (Mobarak et al, 2019). However, these techniques are subject to both ethical and safety concerns (Adashi & Cohen, 2018).…”
Section: Mitochondrial Legacymentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the large impact of abnormal mitochondrial function on oocyte and embryo development has also led to new research looking at the effects of mitochondria replacement therapy. The thought behind these techniques, which can include pronuclear transfer, spindle transfer, ooplasm transfer, or mitochondrial microinjection, is that the mutant or defective mitochondria can be replaced or augmented with healthy donor mitochondria (Mobarak et al, 2019). However, these techniques are subject to both ethical and safety concerns (Adashi & Cohen, 2018).…”
Section: Mitochondrial Legacymentioning
confidence: 99%
“…In addition, mouse studies yielded progeny from mitochondria replacement procedures designed to overcome mitochondrial genetic defects (Adashi & Cohen, 2018; Sato et al, 2005). These methods generally had low mtDNA carryover, but heteroplasmy can be seen in progeny (Mobarak et al, 2019). However, studies to date from mitochondrial microinjection indicate that benefits may be limited in some contexts and may be affected by the cellular source of the mitochondria (Igarashi et al, 2016; Mobarak et al, 2019).…”
Section: Mitochondrial Legacymentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are a major factor in the oocyte quality and are vital in the supply of sufficient ATP, but these may be directly affected during ovarian aging [1,11]. Although mitochondria have been hypothesized to be involved in energy metabolism, calcium homeostasis, growth and apoptosis [12,24,25], they have also been indicated to be the main source of intracellular ROS production [26,27]. Previous studies have reported that as age increases, the oocyte mass decreases, and mitochondrial dysfunction, oocyte mtDNA mutation, and deletion levels increase [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…AUGMENT described the Autologous Germline Mitochondrial Energy Transfer (AUGMENT). Their protocol involves isolation of mitochondria from the patient’s oogonial stem cells (OSCs), processed and injected into the patient’s own oocytes during ICSI [ 129 , 130 , 131 ]. The respective results failed to show an effectiveness through this novel technique, suggesting that it may be possible that the autologous mitochondrial transfer is suitable for a specific population that still remains to be identified.…”
Section: Managing Poor Ovarian Responsementioning
confidence: 99%